#TITLE_ALTERNATIVE# - Widodo (MM : 231 00 040), Achmad
Absract: This thesis is concerned with the use of rotor dynamics as a tool to predict numerically of dynamics behavior of shaft-rotor system on rotating machineries. In examples, the dynamics behaviors are natural frequency as a function of speed rotation, mode shape and vibration response. The simple model and its analytical equations are presented to know the basic phenomena of rotor-shaft system. Then finite element model is made to industrial applications of rotor system. Numerical predictions of dynamics behaviors of pump and turbocharger rotors are selected as examples of industrial applications. The result of numerical prediction presented as Campbell diagram where natural frequencies are function of the speed rotation and mode shape at speed of operation. The mass unbalance response and rotor deflection also will be shown as a consequence of mass unbalance location.